The Local Customary Law: The Contribution of Adat Law in Preserving the Lubuk Larangan in Jambi - Dwi Suryahartati; Firya Otaviarni; Windarto Windarto; Sukamto Satoto; Suhermi Suhermi (Faculty of Law, Jambi University, 2021)
This article discusses the living law which stands behind the Lubuk Larangan tradition in Jambi, Indonesia. While many academics stand on belief that Lubuk Larangan is about the conservation, the article argues there is a metaphysical belief and sacred agreement that triggers such conservation by the indigenous people. Such belief has been overlooked by academics resulting in the failure of seeing the very fundamental life of the indigenous people, as long as their legal practice is concerned. This article demonstrates that the customary law norms can be found in the customary seloko of Jambi Malay, norm which is reflected the whole lives of the indigenous people, both in private and public lives. This article found that the tradition demonstrates a communal way of living and togetherness based on the need of the community. The natural conservation is nothing but the reflection of the sacred, mystic, religious adat and law to keep the nature survive